A Colorimetric Minisequencing Assay for the Mutation in Codon 506 of the Coagulation Factor V Gene - Sitbon, Gisela; Hurtig, Maria; Palotie, Aarno; Lӧnngren, Jӧrgen; Syvӓnen, Ann-Christine (Thrombosis and Haemostasis, 1997)
We describe a colorimetric screening method for the mutation in codon 506 of the coagulation factor V gene. The nucleotide at the site of the FV:Q506 mutation is identified in an immobilized amplified DNA template by extension of a primer with a hapten-labelled dNTP using a DNA polymerase. The incorporated hapten is detected by an antibody- alkaline phosphatase conjugate that catalyses the formation of a coloured end product. The assay is carried out in a microtiter plate format, and the procedure is identical to that of enzyme immunoassays. It unequivocally identifies the FV:Q506 mutation in heterozygous and homozygous form. The colorimetric minisequencing method gave the same result as a 3H-based minisequencing assay and restriction site analysis with Mnll used as reference methods. Because of its simple format and numeric result, the novel colorimetric minisequencing method should be an attractive alternative for screening for the FV:Q506 mutation in clinical laboratories.